Shadow banking: Financial intermediation beyond banks - Esa Jokivuolle (SUERF - The European Money and Finance Forum, 2018)
Shadow banking is a broad concept. A possible definition is that it comprises non-bank institutions which undertake bank-like activities. Another characteristic is that the sector is overall less regulated. Therefore there are still shortcomings in systematic collection of information of the sector.
Keywords: E32; E44; E58; E61; G00; G01; G10; G11; G21; G23; G28; G38; F34; F41; 330; Asset management; Bank Runs; Banking Regulation; Capital Requirements; Chinese financial regulation; credit risk transfer; Crowdfunding; Deposit Insurance; Disintermediation; economic growth; Financial crisis; Financial Intermediation; FinTech; fire sales; Information economics; investment; Leakage; liquidity; Macroprudential Policies; Mutual funds; Securitization; Security design; Shadow Banking; Shadow banking system; Risk measures; Spillovers; Systemic risk; Traditional Banking